Tensile and fatigue behaviors of hybrid laser welded A7N01 alloy with repairing for railway vehicles. (January 2023) - Wu, Zhengkai; Zhou, Xiru; Ao, Ni; Han, Xiaohui; Zhu, Zongtao; Wu, Shengchuan
Highlights: Hybrid laser heat source was selected for repairing of hybrid laser welded A7N01 alloy. Defects in original joints were effectively eliminated by hybrid laser heat source. HCF property with a little increase can be obtained compared with original joints. Abstract: As one of the key concerns in the health maintenance system for modern railway equipment, defect repair plays an important role in enhancing the running safety reliability and economic benefits. In this study, welding defects of A7N01 alloy commonly used in high-speed trains were repaired by hybrid laser welding. The surface integrity of the welded zone before and after repairing was evaluated by various characterization methods in terms of the microstructures, tensile and fatigue properties. The results show that the original incomplete penetration defects would be eliminated by welding repair, giving rise to some microstructural changes such as the grain refinement and the widening of fine grain zone in the original welded joints. The heat input during welding repairing induced significantly reduction of the hardness and tensile strength from 105 HV to 75 HV and from 358 MPa to 338 MPa, respectively. Nevertheless, the fatigue properties of hybrid welded A7N01 alloy with the hybrid welding repairing were improved by 33.8%, probably because of reduced defects.